(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to evaluate the complication rate, length of stay, and associated factors in laparoscopic repair of gastric perforation at Nguyen Tri Phuong Hospital. Materials and Methods: A retrospective case series study was conducted on 62 patients diagnosed with gastric perforation and indicated for laparoscopic surgery from January to December 2018. Data collected included treatment characteristics, complications, length of stay, and postoperative outcomes. Statistical analysis was performed using Stata to examine associations between risk factors and treatment outcomes. Results: A total of 62 patients were included, with a mean age of 50.0 ± 16.6 years. The median surgery duration was 63 minutes, with first flatus on day 2 and drain removal on day 4. The mean length of stay was 9.3 ± 4.0 days. The postoperative complication rate was 21%, with wound infection and pneumonia being the most common. Prolonged hospital stay was associated with older age (p = 0.004), elevated preoperative blood glucose (p = 0.028), perforation size >10 mm (p = 0.036), and delayed surgery (p = 0.036). Logistic regression revealed that advanced age increased complication risk (p = 0.018), while lower WBC levels were linked to higher complications (p = 0.044). Conclusion: Laparoscopic surgery for gastric perforation at Nguyen Tri Phuong Hospital reported an average length of stay was 9.3 ± 4.0 days, associated with several factors such as advanced age, elevated preoperative blood glucose levels, and large perforation size. The postoperative complication rate was 21%. Surgeons need to consider risk factors preoperatively to optimize treatment.